توظيف قنوات اليوتيوب في الدعوة إلى الله - قناة دعوة أنموذجا- - رفيقة, غنايم; السيماء, مصطفاوي (University of Eloued جامعة الوادي, 2019)
تهدف هذه الدراسة الموسومة بتوظيف قنوات اليوتيوب في الدعوة إلى الله- قناة دعوة أنموذجا-، إلى بيان كيفية توظيف واستغلال موقع اليوتيوب في الدعوة إلى الله، وذلك من خلال تحليل محتوى قناة دعوة، وانطلاقا من الإجابة على إشكالية مفادها: كيف يتم توظيف قناة دعوة على اليوتيوب في الدعوة إلى الله؟ وقد اعتمدنا فيها على المنهج الوصفي التحليلي، باستخدام أداة تحليل المضمون لجمع البيانات، حيث كان مجتمع الدراسة مكونا من 2647 مقطع فيديو، اخترنا منه 50 مفردة بطريقة قصدية، وجرى تحليلها وفقاً لاستمارة تحليل المضمون التي تم تحكيمها من طرف أساتذة مختصين في الدراسات الإعلامية، وتوصلنا من خلالها إلى أن قنوات اليوتيوب لها دور مهم وفعال في الدعوة إلى الله وبخاصة قناة دعوة على اليوتيوب ساهمت بشكل كبير في نشر الإسلام على هذا الموقع. This study is titled Employing YouTube Channels in the Call to Allah - call channel as a model -. It aims to show how to employ and exploit YouTube's website in the call to Allah by analyzing the content of the call channel from the answer to the problem: How to employ call channel on YouTube in the call to Allah? We have relied on the analytical descriptive approach, using the content analysis tool to collect data. The community of the study consisted of 2647 video clips; we chose 50 samples in a deliberate way. They were analyzed according to the content analysis form accordance with the content analysis form, which was judged by professors specialized in media studies. We have reached through that the channels of YouTube have an important role and effective in the call to Allah, especially call channel on YouTube which contributed significantly to the spread of Islam on this site.
مذكرة ماستر تخصص دعوة واعلام
Keywords: توظيف، قنوات، اليوتيوب، الدعوة; Employing – Channels – YouTube – the Call